An Authentic, Practice-Based Assessment as a Catalyst for Continuous Professional Development - Sandra Winkelbauer (MDPI AG, 2020)
Over the last ten years, pharmacy practice has changed significantly in Canada. It is more important than ever to ensure that the profession engages in continuing professional development in order to keep up with changing practice and changing public demand and scrutiny. The question is, how do we ensure that the required continual professional development occurs and is applied to practice? One Canadian regulator, the Ontario College of Pharmacists, has attempted to address this question by assessing the success of a number of quality assurance options in terms of addressing the competence of pharmacists, and by extension their ability to learn and apply their learning in an ongoing manner. This case study presents three policy options; an analysis of those options; and finally, an evaluation of the best option for this regulator. The policy alternatives considered include a continuing education/professional development requirement, standardized simulated assessment (i.e., observed structured clinical examination) and authentic practice-based assessment. For the Ontario College of Pharmacists, an authentic practice-based assessment approach seems effective at stimulating quality improvements in pharmacists’ practice, likely because the assessment acts as a catalyst for pharmacists to engage in continuing professional development in order to maintain competence.